Penafsiran Sayyid Quthb Tentang Wacana Pluralisme Agama Dalam Al-Qur’an Surat Al-An’am Ayat 108 Pada Tafsir Fi Zhilal Al-Qur’an - Muhammad Subki; Fitrah Sugiarto; M. Nurwathani Janhari (UIN Mataram, 2021)
Difference is a necessity that Allah created. Humans on this earth are created differently to get to know each other, understand each other's differences and as a test for us who are destined to live in a multicultural society. Lately we are often faced with problems of intolerance that occur, one of which is due to the maturity attitude of some people in responding to differences, especially in terms of religious pluralism. This paper will explain about pluralism according to Sayyid Qutb's interpretation in the book Tafsir Fi Zhilal Al-Qur'an in Surah Al-An'am verse 108. The research methodology used is the Qualitative Descriptive Method, namely by collecting, describing and analyzing data descriptively for get explanations that lead to conclusions. The results of this research are that as believers, we are asked to maintain our individual personalities, always do good deeds, maintain monotheism and respond to differences with maturity and avoid mutually criticizing behavior among other religious groups. This is intended so that security and peace on this earth are well maintained